Food Choices : The ultimate teen guide - Brancato, Robin F. (Lanham, Md. : Scarecrow Press, 2010)
This book discusses numerous topics related to food and eating, including the biological and chemical reasons we prefer certain foods and the eating habits that are unique to teens today. Throughout, teens are presented with the best tips on how to develop healthy eating habits for a lifetime of enjoying food.
So nice here at the top of the food chain -- What kind of eater are you? -- What does your body need? -- The great weight debate -- Family eating -- Bringing food home -- How safe is the food you eat? -- Want to cook? -- What did you eat in school today? -- Eating out -- Going to extremes -- Eating around the world -- The future of food.
Includes bibliographical references and index.
Keywords: Nutrition -- Juvenile literature; Teenagers -- Health and hygiene -- Juvenile literature